Problematics of Labor Absorption of Hospitality Student Training Graduates Teluk Bintuni District in The Job Market - Supriyanto, Slamet (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
The Teluk Bintuni Regency Government is committed and serious in its efforts to deal with female workers who have not yet found work by carrying out Hospitality training activities, to get workers who are trained and educated and have a good attitude. In this writing, the method used is descriptive qualitative, where the author was involved in the training process, interviewing female students and business actors to get a direct picture of the obstacles faced so far. The absorption of trained workers is very important because it can be used as an indicator of the success of the training results so far. The success of labour absorption is influenced by factors such as the individual himself, the environment, family, culture, job opportunities, positive values of the company, and the government as a policy maker, especially in providing job opportunities and protection for native workers. Synergy cooperation between training institutions that produce skilled workers, individuals who have good Attitude, Skills and knowledge will be beneficial if the roles of individuals, families, culture, Companies and the government run well and are mutually beneficial.